Regime types or party systems: what matters more for political instability in the developing world? - Md. , Moniruzzaman (Macrothink Institute, 2015)

(untitled)
Political stability is desired by every state. But is it contingent upon regime types or party systems? Existing studies on political stability suggest that regimes such as authoritarianism, democracy, and dictatorship and their variants have variously influenced political stability. Some have proved to be friendly with political stability in certain countries, while counterproductive for some other. However, the existing literature has exclusively focused on regime types alone neglecting the factor of party systems. This article argues that not only regime types but party systems also influence political stability. Based on data from Asia, Africa and Latin America this article examines the following four assumptions. Firstly, absolute monarchy and absolute authoritarianism together with no or one party system generally maintain political stability. Secondly, constitutional monarchies together with multiparty system generally maintain political stability. Thirdly, presidentialism together with dominant party system generally maintains political stability. And finally, parliamentarianism together with multi-party system is generally negatively related with political stability. Keywords: political instability, regime, party system, developing world